Peningkatan Kemampuan Memecahkan Masalah melalui Media Komputer dalam Pembelajaran Matematika pada Siswa SMKN 1 Ngawen - Haryanto, Urip (Faculty of Engineering, Universitas Negeri Yogyakarta, 2015)
This study aims at improving the students’ problem solving ability of Mathematics through computer-based learning, particularly in the space figures competency at SMK Negeri 1 Ngawen Gunungkidul. This study is categorized as classroom action research. The subjects of the study were the grade XI OC students of SMK Negeri 1 Ngawen Gunung Kidul. The study consisted of repetitious cycles. Every cycle consisted of problem identification, planning, action, observation, and reflection. The results of the study showed that: (1) the application of computer-based learning could improve the students’ problem solving ability of Mathematics and affected positively on the students’ achievement. The improvement was resulted from the conducive learning atmosphere (2) the students were highly interested in computer-based learning. They were more enthusiastic because they were able to confirm the answers directly; (3) to deal with the texts’ low legibility due to the mismatch between the background and the font size, the narration orally explained by the researcher was employed (4) the application of quizzes could motivate the students. They get involved actively in answering questions. The learning activities were more varied.